Innovation and productivity in the colombian service and manufacturing industries (2015)
The knowledge of the innovation-productivity relationship in Latin America, and particularly in the Colombian service sector, is scant. In this study, we explore such relationship comparing the Colombian service industry with manufacturing. Following the Crépon-Duguet-Mairesse empirical approach, the four major findings are as follows: Indeed, Colombian service firms undertake (technological and nontechnological) innovation processes. Regardless of the industry, the probability of innovation increases when there is investment in research and development (R and D) labs and firms are large. The more intensive innovation investment is, the higher the probability of innovation implementation. Finally, labor productivity is enhanced after the introduction of innovations. Copyright © Taylor and Francis Group, LLC.